2015
DOI: 10.1002/pro.2810
|View full text |Cite
|
Sign up to set email alerts
|

A critical element of the light‐induced quaternary structural changes in YtvALOV

Abstract: YtvA, a photosensory LOV (light-oxygen-voltage) protein from Bacillus subtilis, exists as a dimer that previously appeared to undergo surprisingly small structural changes after light illumination compared with other light-sensing proteins. However, we now report that light induces significant structural perturbations in a series of YtvA-LOV domain derivatives in which the Ja helix has been truncated or replaced. Results from native gel analysis showed significant mobility changes in these derivatives after li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Unexpectedly, in none of the published structures or models, two acidic residues localized on strand H β , E105 and D109, conserved within YtvA‐like proteins and involved in signal transduction are part of the dimer interface. Different Bs YtvA constructs have been recently studied by means of native gel analysis, under dark and light conditions . The LOV domain without J α ‐linker (but with the N‐cap) appears to be homodimeric in the dark, but mainly monomeric after light activation; the presence of the J α ‐linker ensured stable dimerization under both light and dark conditions, as previously reported for the full‐length protein .…”
Section: Exploiting Modularity In Signal Transmissionmentioning
confidence: 69%
See 1 more Smart Citation
“…Unexpectedly, in none of the published structures or models, two acidic residues localized on strand H β , E105 and D109, conserved within YtvA‐like proteins and involved in signal transduction are part of the dimer interface. Different Bs YtvA constructs have been recently studied by means of native gel analysis, under dark and light conditions . The LOV domain without J α ‐linker (but with the N‐cap) appears to be homodimeric in the dark, but mainly monomeric after light activation; the presence of the J α ‐linker ensured stable dimerization under both light and dark conditions, as previously reported for the full‐length protein .…”
Section: Exploiting Modularity In Signal Transmissionmentioning
confidence: 69%
“…Instead, thermal grating measurements showed no light‐induced conformational changes for the LOV core, at least on the ms timescale, but comparable changes (within 70 μs) when the N‐cap alone or N‐cap + J α ‐linker is present . Choi et al ., nevertheless, could not detect any change in extent of oligomerization by means of size exclusion chromatography (SEC), in partial discrepancy with the native gel analysis . We may add here that in the short‐LOV protein Rs LOV (Rs = Rhodobacter sphaeroides ), the dark state is dimeric, with A′ α and J α forming an unusual helical bundle, whereas light excitation results in monomerization of Rs LOV, as revealed by small‐angle X‐ray scattering and cross‐linking studies .…”
Section: Exploiting Modularity In Signal Transmissionmentioning
confidence: 79%
“…LG1 bears the same YtvA‐LOV domain, including regions flanking the LOV core, i.e. the short helical N‐terminus and the C‐terminally positioned J‐helical linker, both being structural elements essential for dimerization of the LOV domain and thereby also ensuring dimerization of the full‐length protein .…”
Section: Resultsmentioning
confidence: 99%
“…LG1 bears the same YtvA-LOV domain, including regions flanking the LOV core, i.e. the short helical N-terminus and the C-terminally positioned J-helical linker, both being structural elements essential for dimerization of the LOV domain and thereby also ensuring dimerization of the full-length protein (34). Hints on the possible structure of LG1 were obtained by a two-step domain docking approach starting with a LOV-LOV docking using Cluspro software (35).…”
Section: Structural Aspects For Lg1mentioning
confidence: 99%
“…However, the activation of the kinase domain is neither accompanied by protonation changes nor changes in the strength of the hydrogen bond network of carboxylic side chains . Recent studies showed that YtvA is a dimer independent on its activation state . However, size exclusion chromatography (SEC) and circular dichroism (CD) spectroscopy on aureochrome 1 demonstrated that dimerization of the LOV domains upon light illumination leads to activation of the sensor domain .…”
Section: Introductionmentioning
confidence: 99%